Direct‐geneFISH: a simplified protocol for the simultaneous detection and quantification of genes and rRNA in microorganisms - Barrero‐Canosa, Jimena; Moraru, Cristina; Zeugner, Laura; Fuchs, Bernhard M.; Amann, Rudolf (Environmental microbiology, 2017)
Summary Although fluorescence in situ hybridization (FISH) with specific ribosomal RNA (rRNA)‐targeted oligonucleotides is a standard method to detect and identify microorganisms, the specific detection of genes in bacteria and archaea, for example by using geneFISH, requires complicated and lengthy (> 30 h) procedures. Here we report a much improved protocol, direct‐geneFISH, which allows specific gene and rRNA detection within less than 6 h. For direct‐geneFISH, catalyzed amplification reporter deposition (CARD) steps are removed and fluorochrome‐labelled polynucleotide gene probes and rRNA‐targeted oligonucleotide probes are hybridized simultaneously. The protocol allows quantification of gene copy numbers per cell and the signal of the directly labelled probes enables a subcellular localization of the rRNA and target gene. The detection efficiencies of direct‐geneFISH were first evaluated on Escherichia coli carrying the target gene on a copy‐control vector. We could show that gene copy numbers correlated to the geneFISH signal within the cells. The new protocol was then applied for the detection of the sulfate thiolhydrolase (soxB) genes in cells of the gammaproteobacterial clade SUP05 in Lake Rogoznica, Croatia. Cell and gene detection efficiencies by direct‐geneFISH were statistically identical to those obtained with the original geneFISH, demonstrating the suitability of the simpler and faster protocol for environmental samples.